Model Pengeluaran Rumahtangga Peternak Ayam Broiler Di Kecamatan Tenayan Raya Kota Pekanbaru Provinsi Riau - Elinur, Elinur; Heriyanto, Heriyanto; Bakce, Djaimi; Arief Wahyudi, Hajry; Rahmadani, Elfi (Politeknik Negeri Lampung., 2024)
Household expenditure is the amount of money used by households to meet household consumption. This study aims to analyze the characteristics of broiler farmers, the structure of household income and expenditure, and analyze the factors affecting broiler farmers household expenditure. This study uses a survey method. The sampling method used simple random sampling with a total sample of 56 broiler farmers. There are 4 findings in this study. First, the age of the broiler farmers is productive with a high school education level. They are experienced in their business. Second, the structure of broiler farmers household income consists of broiler business income and non-farm income. Broiler business income has a large contribution to household income. Third, household expenditure consists of food and non-food expenditure. Non-food expenditure has the largest share of household expenditure. Fourth, significant dominant factors affecting household expenditure are household income, number of family members, savings and household assets. However, farmer's education does not significantly affect household expenditure